Regional techniques for paediatric inguinal scrotal surgery. A randomized non-inferiority trial comparing low concentration caudal block versus ilioinguinal and iliohypogastric nerve block. - H-Y. Wong; T. Beaney; M. Shah; M. Pinnock; K. Veerappan (Pediatric Anesthesia and Critical Care Journal (PACCJ))
Introduction We have designed a prospective, randomised, single blinded non-inferiority trial to determine whether using a lower concentration local anaesthetic in caudal blocks (0.125% levobupivacaine) provides non-inferior analge- sia compared to IG/IH blocks with fewer side effects. Material and methods We recruited 82 patients for our study at Medway Mari- time Hospital. The intervention was caudal block with 0.125% levobupivacaine with clonidine as an additive compared with USS guided IG/IH nerve blocks. Our pri- mary outcome measure was post-operative pain and our predefined non-inferiority margin was a 15% difference in pain. Secondary outcomes included rescue analgesia, motor block, time to discharge and micturition. Results 80 patients were included in analysis (caudal n=40, IG/IH n=40). We found a 5% absolute decrease in post-opera- tive pain after low concentration caudal blocks compared to IG/IH blocks (95% CI -19.5 to 9.5, p <0.01) demon- strating non-inferiority. There was no evidence of non- inferiority for motor block, with 12.5% more patients ex- periencing motor block in the caudal group immediately following recovery from general anaesthetic (95% CI - 2.4 to 28.4 p=0.379 for non-inferiority). Of these, 2 pa- tients receiving caudal blocks (5%) had remaining motor block on the ward which recovered by discharge. Conclusions Our study shows non-inferiority between low concentra- tion local anaesthetic in caudal blocks compared with USS guided IG/IH nerve blocks for analgesic benefit and requirement for post-operative analgesia. We suggest 0.125% levobupivacaine for anaesthetists who use caudal blocks in their practice. This technique demonstrates non-inferiority compared to USS guided IG/IH blocks.